Hybrid Hamiltonian Simulation Approach for the Analysis of Quantum Error Correction Protocol Robustness - Benjamin Gys; Lander Burgelman; Kristiaan De Greve; Georges Gielen; Francky Catthoor (IEEE Transactions on Quantum Engineering)
The development of future full-scale quantum computers (QCs) not only comprises the design of good quality qubits, but also entails the design of classical complementary metal–oxide semiconductor (CMOS) control circuitry and optimized operation protocols. The construction and implementation of quantum error correction (QEC) protocols, necessary for correcting the errors that inevitably occur in the physical qubit layer, form a crucial step in this design process. The steadily rising numbers of qubits in a single system make the development of small-scale quantum architectures that are able to execute such protocols a pressing challenge. Similar to classical systems, optimized simulation tools can greatly improve the efficiency of the design process. We propose an automated simulation framework for the development of qubit microarchitectures, in which the effects of design choices in the physical qubit layer on the performance of QEC protocols can be evaluated, whereas the focus in the current state-of-the-art design tools only lies on the simulation of the individual quantum gates. The hybrid Hamiltonian framework introduces the innovative combination of a hybrid nature that allows to incorporate several levels throughout the QC stack, with optimized embedded solvers. This provides the level of detail required for an in-depth analysis of the QEC protocol's stability.